1979
DOI: 10.1007/bf01382370
|View full text |Cite
|
Sign up to set email alerts
|

The colloidal behaviour of kraft lignin

Abstract: The colloidal behaviour of kraft lignin Part I.: Association and gelation of kraft lignin in aqueous solutions T. LindstrSm

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
61
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 30 publications
4
61
0
1
Order By: Relevance
“…The aggregation and hydrodynamic radius of colloidal lignin in aqueous solution can be influenced by many factors, such as pH [28,29], temperature [30], electrolyte [31,32], concentration of lignin [33] and surfactant [34]. Due to the ionizable phenolic hydroxyls and carboxylic groups in lignin macromolecules, the association and particle size of lignin are very sensitive to the solution pH.…”
Section: Results and Discussion 31 Effect Of Ph On The Particle Sizmentioning
confidence: 99%
See 1 more Smart Citation
“…The aggregation and hydrodynamic radius of colloidal lignin in aqueous solution can be influenced by many factors, such as pH [28,29], temperature [30], electrolyte [31,32], concentration of lignin [33] and surfactant [34]. Due to the ionizable phenolic hydroxyls and carboxylic groups in lignin macromolecules, the association and particle size of lignin are very sensitive to the solution pH.…”
Section: Results and Discussion 31 Effect Of Ph On The Particle Sizmentioning
confidence: 99%
“…When the pH is low enough and carboxylic groups are completely protonated, the serious aggregation of lignin particles is unavoidable. It can be attributed that the attractive forces including hydrophobic interactions, hydrogen bonding interactions [28] and !-! interactions [36][37][38][39] surpass the electrostatic repulsive forces.…”
Section: Results and Discussion 31 Effect Of Ph On The Particle Sizmentioning
confidence: 99%
“…Furthermore, Lindström reported the presence of stable lignin sols in aqueous solution whose extent of aggregation was followed by gel permeation chromatography (GPC) and viscometric measurements; however, no light scattering measurements were made. Lindström 10 explained the aggregation (sol or gel formation) by hydrogen bonding between neighboring lignin group carboxylic groups, ether oxygens, and hydroxylic groups. It was found that the extent of aggregation of kraft lignin sols in the hydrogen form increases with increasing storage time and temperature.…”
Section: Introductionmentioning
confidence: 99%
“…It is rather difficult to get a general picture of the exact shape and the actual size of an isolated lignin particle. In addition, there are strong hydrogen bonding interactions [13,14] and "-" interactions [15] in lignin molecules, thereby resulting in serious thermally irreversible aggregation when lignin is recovered from solutions. As a consequence, it is rather difficult to obtain nanostructured lignin.…”
Section: Introductionmentioning
confidence: 99%
“…Especially in nonpolar polymer matrix, very few efforts have been made to obtain highly exfoliated MMT [29]. Commonly, lignin in solution is assumed to be an approximately spherical microgel between that of an Einstein sphere and a linear nonfree-draining random coil with different hydrodynamic sizes from several nanometers to several hundred nanometers [13]. While spread out in a monolayer or adsorbed onto a surface, lignin is envisaged as being made up of flexible, disk-like molecules having various shapes and sizes but all with approximately the same thickness of 2 nm [30].…”
Section: Introductionmentioning
confidence: 99%